Short- and Long-Run Impacts of Food Price Changes on Poverty - Ivanic, Maros; Martin, Will (World Bank Group, Washington, DC, 2014)
This study uses household models based on detailed expenditure and agricultural production data from 31 developing countries to assess the impacts of changes in global food prices on poverty in individual countries and for the world as a whole. The analysis finds that food price increases unrelated to productivity changes in developing countries raise poverty in the short run in all but a few countries with broadly-distributed agricultural resources. This result is primarily because the poor spend large shares of their incomes on food and many poor farmers are net buyers of food. In the longer run, two other important factors come into play: poor workers are likely to benefit from increases in wage rates for unskilled workers from higher food prices, and poor farmers are likely to benefit from higher agricultural profits as they raise their output. As a result, higher food prices appear to lower global poverty in the long run.